Orwin, Isabell (audio interview #3 of 3) - Orwin, Isabell (b. 12/16/1904 - d. 7/2/2000); Fischer, Jan, interviewer
INTERVIEW DESCRIPTION - This is the last of three interviews with Isabell Orwin conducted in the front room of her old-style bungalow home. The dark paneled living room is filled with momentos of her Lockheed years, which she enjoyed showing off. Orwin still sported the reddish hair seen in many of her photographs, and dressed up for the interviews. A very cordial person, she greatly enjoyed the interview and was very forthcoming. 1/21/1981